Active explosion barrier performance against methane and coal dust explosions - du Plessis, J. J. L. (International journal of coal science & technology, 2015)
Preventing the propagation of methane or coal dust explosions through the use of active explosion-suppression systems remains one of the most underutilised explosion controls in underground coal mines. As part of the effort to develop better technologies to safeguard mines, the use of active barrier systems was investigated at Kloppersbos in South Africa. The system is designed to meet the requirements of the European Standard （EN 14591-4 2007） as well as the Mine Safety Standardisation in the Ministry of Coal Industry, Coal Industrial 1 Standard of the Peoples Republic of China （MT 694-1997）. From the tests conducted, it can be concluded that the ExploSpot System was successful in stopping flame propagation for both methane and methane and coal dust hybrid explosions when ammonium phosphate powder was used as the suppression material. The use of this barrier will provide coal mine management with an additional explosion control close to the point of ignition and may find application within longwall faces further protecting mines against the risk of an explosion propagating throughout a mine.